2012
DOI: 10.3892/or.2012.1685
|View full text |Cite
|
Sign up to set email alerts
|

SNAI1 overexpression induces stemness and promotes ovarian cancer cell invasion and metastasis

Abstract: Abstract. Ovarian cancer is the fifth most common cancer among women worldwide. Detection of metastasis of ovarian cancer is crucial for diagnosis and prolongs the life of patients. This study focused on whether SNAI1 overexpression relates to invasion of ovarian cancer in vitro and in vivo. Invasion, colony formation and wound healing assays and flow cytometric analysis were performed to test the invasion and proliferation of SKOV3 ovarian cancer cells after transfection. The effect of SNAI1 on ovarian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…It has been suggested that activation of AKT will lead to degradation of SNAIL ultimately leading to EMT and increased invasiveness. However in SKOV3 cells SNAIL overexpression has been reported to increase invasiveness [56]. The decrease of invasiveness after MAEL overexpression observed in the present study could be due to a reduction in SNAIL activity by MAEL.…”
Section: Discussioncontrasting
confidence: 43%
“…It has been suggested that activation of AKT will lead to degradation of SNAIL ultimately leading to EMT and increased invasiveness. However in SKOV3 cells SNAIL overexpression has been reported to increase invasiveness [56]. The decrease of invasiveness after MAEL overexpression observed in the present study could be due to a reduction in SNAIL activity by MAEL.…”
Section: Discussioncontrasting
confidence: 43%
“…Our data suggest that there is a reciprocal interaction between EMT-like processes and CD73 enzymatic activity in GSCs. SNAIL1 has been described to promote the invasive and clonogenic capacities of GBM tumours [37]. Thus, the reduced SNAIL1 expression diminishes mesenchymal properties of CD73 knockdown cells, demonstrated by their significantly decreased invasiveness and clonogenicity.…”
Section: Discussionmentioning
confidence: 95%
“…Although KLHDC7B is reported to be highly expressed in breast cancer, its functions are not well studied 27 . Enriched Set 2 TFs (PRRX1-SNAI1-SNAI2-ZEB1-ZEB2-TWIST1) are extensively studied in the context of cell migration during embryonic development and tumor metastases and mediate EMT 28 29 30 31 32 . These TFs are also additionally known to be associated with other features besides EMT including oncogenic transformation, resistance to apoptosis and senescence, cancer cell stemness, and can also promote tumor angiogenesis 33 34 35 36 .…”
Section: Resultsmentioning
confidence: 99%